2017
DOI: 10.1038/s41598-017-11225-w
|View full text |Cite
|
Sign up to set email alerts
|

The Chemical Form of Metal Species Released from Corroded Taper Junctions of Hip Implants: Synchrotron Analysis of Patient Tissue

Abstract: The mechanisms of metal release from the articulation at the head cup bearing and the tapered junctions of orthopaedic hip implants are known to differ and the debris generated varies in size, shape and volume. Significantly less metal is lost from the taper junction between Cobalt-Chromium-Molybdenum (CoCrMo) and Titanium (Ti) components (fretting-corrosion dominant mechanism), when compared to the CoCrMo bearing surfaces (wear-corrosion dominant mechanism). Corrosion particles from the taper junction can lea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
18
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 48 publications
3
18
0
Order By: Relevance
“…Previous studies investigating chemical composition of tissues surrounding MoM and MoP hip implants reported on the presence of Co II complexed with organic ligands in an octahedral environment (e.g. Co:MPG complex) [16,17,28]. In the current study, most Co XANES spectra resembled Co II , but we were unable to establish the exact chemical form of the metal due to poor data quality.…”
Section: Analysis Of Co Xanes Spectramentioning
confidence: 58%
See 2 more Smart Citations
“…Previous studies investigating chemical composition of tissues surrounding MoM and MoP hip implants reported on the presence of Co II complexed with organic ligands in an octahedral environment (e.g. Co:MPG complex) [16,17,28]. In the current study, most Co XANES spectra resembled Co II , but we were unable to establish the exact chemical form of the metal due to poor data quality.…”
Section: Analysis Of Co Xanes Spectramentioning
confidence: 58%
“…Tissues surrounding Ti alloy implants have been found to contain TiO2 in either anatase, rutile [56] or amorphous form [17]. Our investigation identified TiO2 in most of the systemic tissue samples.…”
Section: Analysis Of Ti Xanes Spectramentioning
confidence: 65%
See 1 more Smart Citation
“…The presence of chromium phosphate, Cr 2 O 3 and CoCr particles in tissue samples from around failing hip prostheses with evidence of damage at the tapers (Di Laura et al, 2017; Munir et al, 2016; Urban et al, 1994; Wang, 2019; Xia et al, 2017) and cement–stem interfaces (Campbell et al, 2003) has been previously reported. The conditions within the crevice (Gibon et al, 2017) and in the lysosomal compartment inside macrophages can favor particle dissolution and formation of phosphate precipitates, which have been previously found in periprosthetic tissue around hip implants (Di Laura et al, 2017; Urban et al, 2000). The debris investigated in these previous studies, was not processed to release and clean the metal nanoparticles and the imaging and characterization was undertaken at the lower resolution and thus, did not reveal the characteristics of the Cr 2 O 3 nanoparticles, identified in this study.…”
Section: Discussionmentioning
confidence: 82%
“…A comprehensive characterization, therefore, requires the digestion of the flakes to liberate the metal particles to understand about the modes of material loss and corrosion processes at the sites of wear. The investigation of debris released from CoCrMo tapers and cement–stem interfaces, internalized in periprosthetic tissue and macrophages, showed clusters of Cr oxides, Cr phosphates (Di Laura et al, 2017; Urban et al, 1994) and CoCr nanoparticles (Campbell et al, 2003). The harsh conditions in the lysosomal compartments (i.e., acidic pH ~4), however, may change the chemistry of the debris and thus misidentify the species released from the wear sites.…”
Section: Introductionmentioning
confidence: 99%